Structural heterogeneity of a human norovirus vaccine candidate - Devant, Jessica; Hansman, Grant S. (Virology, 2021)
Human norovirus virus-like particles (VLPs) are assumed to be morphologically and antigenically similar to virion particles. The norovirus virion is assembled from 180 copies of the capsid protein (VP1) and exhibits T = 3 icosahedral symmetry. In this study, we showed that the vaccine candidate GII.4c VP1 formed T = 1 and T = 3 VLPs, but mainly assembled into T = 4 icosahedral particles that were composed of 240 VP1 copies. In contrast, another clinically important genotype, GII.17, almost exclusively folded into T = 3 VLPs. Interestingly, the GII.4c T = 1 particles had higher binding capacities to norovirus-specific Nanobodies than to GII.4c T = 3 and T = 4 particles. Our data indicated that the occluded Nanobody-binding epitopes on the T = 1 particles were more accessible compared to the larger T = 3 and T = 4 particles. Overall, this new data revealed that GII.4c VLPs had a preference for forming the T = 4 icosahedral symmetry and future studies with varied sized norovirus VLPs should take caution when examining antigenicity.
Available online 28 October 2020
Gesehen am 08.02.2021